PENGARUH PEMBERIAN MADU TERHADAP KADAR HDL DAN LDL TIKUS PUTIH (Rattus Novergicus L.) JANTAN GALUR WISTAR YANG DIINDUKSI TUAK - ANWARUL , MIZAN; ROBITAH ASFUR; FANY ADE IRMA; MEIZLY ANDINA (LP2MTBM MAKARIOZ, 2019)
Palm wine contains alcohol which increase HDL and LDL levels. Honey has effect on human human health, with antioxidant, bacteriostatic, anti-inflamatory and antimicrobial properties. On the other hand, honey is also known as one of the nutrional sources that are rich in antioxidants. Thus cell regeneration mediated by antioxidants is also expected to increase HDL levels. Objective: to determine the effect of giving honey on HDL and LDL levels of palm wine-induced white male wistar strain rats. Research Method: This research uses True Experiment method with “Pretest-Posttest with control design”. This study used 32 samples of white male wistar strain rats (Rattus novergicus L.) divided into 2 group, 16 controls, and 16 treatment group. This research uses palm wine obtained in Bandar Klippa area, Percut Sei Tuan, Tembung and Sumbawa Forest’s honey terraces. The data obtained will be analyzed by using the test statistic Test of Different in Means (T-Test Dependent and Independent) Result: The result showed that the mean HDL levels in the pre and post-honey control group were 34,8271 mg/dl and 49,1859 mg/dl. Meanwhile, on the mean HDL levels in the pre and post-honey treatment group were 47,0776 mg/dl and 69,3019 mg/dl. The mean LDL levels in the pre and post-honey control group were 61,3338 mg/dl and 54,1831 mg/d, Respectively. In the treatment group, the mean pre-honey LDL levels in the pre and post-honey were 48,7675 mg/dl and 27,2650 mg/dl. Conclusion: Honey can increase HDL levels and decrease LDL levels of palm wine-induced male white wistar strain rats (Rattus novergicus L.)